2020
DOI: 10.3390/ma13122862
|View full text |Cite
|
Sign up to set email alerts
|

Harmony Search Optimisation of Dispersed Laminated Composite Plates

Abstract: One of the major goals in the process of designing structural components is to achieve the highest possible buckling load of the structural component while keeping the cost and weight at a minimum. This paper illustrates the application of the harmony search algorithm to the buckling load maximisation of dispersed laminated composite plates with rectangular geometry. The ply thicknesses and fiber orientation angles of the plies were chosen as the design variables. Besides the commonly used carbon fiber reinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…It aims to obtain a global solution as the perfect state, which is calculated by an objective function [45]. Recently, HS was employed in structural engineering problems such as the optimization of RC frame structures [46], RC beams [47], dispersed laminated composite plates [48], steel plate girders [49], analysis of plane stress systems via total potential optimization [50], and nozzle movement for additive manufacturing of concrete structures and concrete elements [51].…”
Section: Optimization Methodology Using Hsmentioning
confidence: 99%
“…It aims to obtain a global solution as the perfect state, which is calculated by an objective function [45]. Recently, HS was employed in structural engineering problems such as the optimization of RC frame structures [46], RC beams [47], dispersed laminated composite plates [48], steel plate girders [49], analysis of plane stress systems via total potential optimization [50], and nozzle movement for additive manufacturing of concrete structures and concrete elements [51].…”
Section: Optimization Methodology Using Hsmentioning
confidence: 99%
“…A metaheuristic algorithm that found application in diverse areas of engineering is the harmony search technique that was invented by Geem [12]. Initially conceived for the optimization of discrete-valued data, the technique eventually evolved in such a manner that it applies to a wide range of problems including water network design [24,25], analysis of plane stress systems [26], design of retaining walls [27], vehicle routing [28], and stacking sequence optimization of laminated composite plates [29].…”
Section: Harmony Search Algorithmmentioning
confidence: 99%
“…Concerning the choice of optimization technique, Cakiroglu et al [23] have shown that the harmony search (HS) optimization technique was capable of obtaining dispersed stacking sequences that perform better than conventional sequences, such as the [45, −45, 0, 90, 0, 90, 0, −45, 45] fiber angle sequence used by Führer [42]. The present study adopted the optimum stacking sequence from the analyses done by Cakiroglu et al [23] as a starting configuration and further improved this stacking sequence in the presence of cut-outs. In addition to circular cut-outs, the use of rectangular and triangular cut-outs is investigated, including an analysis of the effects of each on the structural performance.…”
Section: Scope and Objectivesmentioning
confidence: 99%
“…All plate configurations have the same length for their shorter sides, which is 150 mm long, resulting in a cut-out area of 1964 mm 2 . As the starting configuration for the stacking sequence, the best-performing layup is taken from the previous study by the authors for all three aspect ratios [23]. These layup configurations are further optimized, and the results are compared to the performance of plates with cut-outs having the regular stacking sequence from Führer [42].…”
Section: Optimization Proceduresmentioning
confidence: 99%
See 1 more Smart Citation